Neuromagnetic motor fields accompanying self-paced rhythmic finger movement at different rates - Mayville, Justine M.; Fuchs, Armin; Kelso, J. A. Scott (Experimental brain research, 2005)
We have studied the effect of movement rate on MEG activity associated with self-paced finger movement in four subjects to determine whether the amplitude or latency of motor-evoked activity changes across a range of rates. Subjects performed a continuation paradigm at 21 distinct rates (range: 0.5-2.5 Hz) chosen because of their relevance for many types of sensorimotor coordination (e.g. musical performance). Results revealed a pair of field patterns whose topography and temporal dynamics were similar across all subjects. The strongest pattern was a movement-evoked field (MEF) that emerged during the response and exhibited one or two polarity reversals in time depending on the subject. The MEF complex was tightly coupled to the biphasic response profile but neither latency nor peak amplitude of each MEF component had significant dependence on the temporal duration between successive responses, i.e. movement rate. In contrast, the maximal amplitude of a second, weaker pattern decreased by over 50% when movement rates exceeded 1.1 Hz (inter-response interval <1 s). This pattern was characterized by a change in field line direction over the midline of the scalp and a gradual accumulation of amplitude prior to movement onset. Both characteristics are suggestive of a readiness field. The observed rate-dependent changes in this field may contribute to known transitions in sensorimotor coordination that emerge when the frequency of coordination is increased.